Calculating Trade in Value Added - Aslam, Aqib (IMF Working Papers; Working Paper ;, 2017)
This paper sets out the key concepts necessary to calculate trade in value added using input-output tables. We explain the basic structure of an input-output table and the matrix algebra behind the computation of trade in value added statistics. Specifically, we compute measures of domestic value-added, foreign value added, and forward and backward linkages, as well as measures of both a country's participation and position in global value chains. We work in detail with an example of a global input-output table for 3 countries each with 4 sectors, provided by the Eora Multi-Region Input-Output (MRIO) database. The aim is to provide an introduction to the analysis of global value chains for use in policy work. An accompanying suite of Matlab codes are provided that can be used with the full set of Eora MRIO tables.